2017
DOI: 10.1186/s40813-017-0054-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a GnRH analogue (peforelin) on the litter performance of gilts and sows

Abstract: BackgroundMaintaining optimal reproductive and litter performance is essential for meeting economic targets in commercial pig production. Treatment with exogenous gonadotropins in sows after weaning or in gilts after altrenogest treatment has been used to stimulate follicular development leading to more piglets born and eventually higher birth weights. The effect of peforelin on litter performance was investigated in 212 gilts, primi- and pluriparous sows in three herds. Animals were randomly allocated to thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Previous studies indicated that PMSG treatments 24 hr after altrenogest removal could not only effectively synchronize oestrus and ovulation (Dura et al., 1987), but also increase ovulation rate (Estienne et al., 2001; Horsley et al., 2005). However, a part of researches showed that the reproductive performance was slightly improved when gilts were treated with PMSG about 42–48 hr after the last altrenogest feeding (de Jong et al., 2013, 2017; Lau et al., 2009). In the present study, the levels of E2 in all of the treatment groups were significantly increased on the third day after PMSG injection, while the levels of P4 remained constant before ovulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that PMSG treatments 24 hr after altrenogest removal could not only effectively synchronize oestrus and ovulation (Dura et al., 1987), but also increase ovulation rate (Estienne et al., 2001; Horsley et al., 2005). However, a part of researches showed that the reproductive performance was slightly improved when gilts were treated with PMSG about 42–48 hr after the last altrenogest feeding (de Jong et al., 2013, 2017; Lau et al., 2009). In the present study, the levels of E2 in all of the treatment groups were significantly increased on the third day after PMSG injection, while the levels of P4 remained constant before ovulation.…”
Section: Discussionmentioning
confidence: 99%
“…Fixed‐time artificial insemination was performed in gilts according to previously established methods, with some modifications (Brussow et al., 1996; de Jong et al., 2013, 2017; Lau et al., 2009; Martinat‐Botte et al., 2010). The ratio of AIS treatment dose to body weight was used as one of the standards and referred to the previous studies (Medan et al., 2004; Nambo et al., 1998; Sasaki et al., 2006; Taya et al., 1996).…”
Section: Methodsmentioning
confidence: 99%
“…The discovery of the GnRH analog's structure and synthesis led to it becoming a potential substitute for hCG and eCG in follicular growth stimulation and ovulation induction (Brüssow et al, 1996). The following GnRH agonists have been tested to stimulate LH secretion and induce ovulation in sows: gonadorelin (Brüssow et al, 1990, 1996), lecirelin (Baruselli et al, 2001); peforelin (Brüssow et al, 2010; De Jong et al, 2017; Hunter et al, 2004), goserelin (Brüssow et al, 2007), buserelin (Driancourt et al, 2013; Martinat‐Botté et al, 2010), and triptorelin (Knox et al, 2011, 2017).…”
Section: Induction and Synchronization Of Ovulation In Sowsmentioning
confidence: 99%
“…, Administering peforelin produced an increase in follicle diameter due to increased FSH during the follicular phase that influenced the size of CL and P4 levels. In addition, homogeneous litters and higher birth weight were obtained through the peforelin treatment rather than the control treatment (1.42 ± 0.38 vs. 1.35 ± 0.35), although the number of live births was lower compared to the control group (12.8 ± 3.3 vs. 13.2 ± 3.6) (de Jong et al, 2017; Hunter et al, 2004).…”
Section: Induction and Synchronization Of Ovulation In Sowsmentioning
confidence: 99%
See 1 more Smart Citation